Mathba’ah Islamiah di Minangkabau: Sejarah Sebuah Penerbit Islam Melintasi Tiga Zaman (1924-1972) - Halimatus Sakdiah (Islam Transformatif : Journal of Islamic Studies, 2020)
This article wants to know the history and development of the Mathba'ah Islamiah publisher from its early days until it disappeared from the circulation of its publishing and printing world. In the 20th century, there were many publishers and printers in Bukittinggi. This arose in response to requests for reading material from educated people connected with schools' growing bloom in several places in West Sumatra. Publishing and printing work was carried out by colonial circles and Western intellectuals and involved natives from within the Muslim faith. The research method used is the historical research method. From the research results, it was found that the publishing of Mathba'ah Islamiah was a publication founded by H.M.S Sulaiman on the advice of the elderly scholars, Syekh Sulaiman Arrasuli, Syekh Muhammad Jamil Jaho and Syekh Abbas Qadhi Lading Laweh. This publication published the works of Minangkabau clerics and books used in the Madrasas of the Old People at that time. Not only publishing books, but the Mathba'ah Islamiah publisher also printed the Koran and its translations sent to various regions in Sumatra and even reached several parts of the archipelago.Artikel ini hendak mengetahui sejarah dan perkembangan penerbit Mathba’ah Islamiah sejak masa awal hingga hilang dari peredaran dunia penerbitan dan percetakan Tanah Air. Pada abad ke-20 terdapat banyak penerbit dan percetakan di Bukittinggi. Hal Penerbitan ini timbul sebagai tanggapan atas permintaan bahan bacaan dari orang terdidik dalam hubungannya dengan tumbuh mekarnya sekolah-sekolah di sejumlah tempat di Sumatera Barat. Kerja penerbitan dan percetakan tidak saja dilakukan oleh kalangan kolonial dan kaum terdirik Barat, tetapi juga melibatkan kaum pribumi dari kalangan agama Islam. Metode penelitian yang digunakan ialah metode penelitian sejarah. Dari hasil penelitian ditemukan bahwa penerbitan Mathba’ah Islamiah adalah penerbitan yang didirikan oleh H.M.S Sulaiman atas anjuran dari ulama kaum tua Syekh Sulaiman Arrasuli, Syekh Muhammad Jamil Jaho dan Syekh Abbas Qadhi Lading Laweh. Penerbitan ini menerbitkan karya-karya ulama Minangkabau dan juga kitab-kitab yang dipakai di madrasah-madrasah Kaum Tua ketika itu. Tak hanya menerbitkan buku-buku saja penerbit Mathba’ah Islamiah ini juga mencetak Al-Quran dan terjemahannya yang dikirim ke berbagai daerah di Sumatra bahkan menjangkau beberapa daerah Nusantara.